Ventricular Tract Hemorrhage Following Intracranial Nail Removal: Utility of Real-time Endovascular Assistance - Rennert, Robert C.; Steinberg, Jeffrey A.; Sack, Jayson; Pannell, J. Scott; Khalessi, Alexander A. (Frontiers in Neurology, 2016)
Penetrating brain trauma commonly results in occult neurovascular injury. Detailed cerebrovascular imaging can evaluate the relationship of intracranial foreign bodies to major vascular structures, assess for traumatic pseudoaneusysms, and ensure hemostasis during surgical removal. We report a case of a self-inflicted intracranial nail gun injury causing a communicating ventricular tract hemorrhage upon removal, as well as a delayed pseudoaneurysm. Pre- and post-operative vascular imaging, as well as intra-operative endovascular assistance was critical to successful foreign body removal in this patient. This report demonstrates the utility of endovascular techniques for the assessment and treatment of occult cerebrovascular injuries from intracranial foreign bodies.